2018
DOI: 10.2147/dddt.s155567
|View full text |Cite
|
Sign up to set email alerts
|

Combined application of tenuigenin and β-asarone improved the efficacy of memantine in treating moderate-to-severe Alzheimer’s disease

Abstract: BackgroundAlzheimer’s disease (AD) is a slowly progressive neurodegenerative disease which cannot be cured at present. The aim of this study was to assess whether the combined application of β-asarone and tenuigenin could improve the efficacy of memantine in treating moderate-to-severe AD.Patients and methodsOne hundred and fifty-two patients with moderate-to-severe AD were recruited and assigned to two groups. Patients in the experiment group received β-asarone 10 mg/d, tenuigenin 10 mg/d, and memantine 5–20 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…In this study, Chang et al . reported that the combined application of β-asarone and tenuigenin could improve the efficacy of memantine in promoting the cognitive function of moderate-to-severe AD patients [ 149 ]. However, this is a small-scale clinical trial, and they did not identify the specific role of β-asarone in this study.…”
Section: Clinical Use Of Natural Constituents From Chinese Herbal Medmentioning
confidence: 99%
“…In this study, Chang et al . reported that the combined application of β-asarone and tenuigenin could improve the efficacy of memantine in promoting the cognitive function of moderate-to-severe AD patients [ 149 ]. However, this is a small-scale clinical trial, and they did not identify the specific role of β-asarone in this study.…”
Section: Clinical Use Of Natural Constituents From Chinese Herbal Medmentioning
confidence: 99%
“…Also, the combined application of β‐asarone and tenuigenin significantly enhanced the efficacy of memantine in treating moderate‐to‐severe Alzheimer's disease (AD) patients. [ 21 ] Furthermore, β‐asarone and levodopa ( l ‐dopa) coadministered therapy significantly relieved some behavioral impairment of PD rats induced by 6‐hydroxydopamine hydrobromide, and it was hypothesized that β‐asarone passed through the blood–brain barrier and increased l ‐dopa concentration in the brain of PD rats. [ 22 ] However, this study was the first to demonstrate the neuroprotective effects of β‐asarone by attenuating neuronal apoptosis and promoting axonal regeneration in scratch‐injured mouse neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Senegenin is a potential drug for AD. Although clinical studies have found that in the treatment of moderate to severe AD, the effect of adding senegenin was significantly enhanced ( Chang and Teng, 2018 ; Dong and et al, 2018 ), there are too few clinical studies. In order to speed up the clinical application of senegenin, there are several key issues that need to be solved:…”
Section: Further Perspectivementioning
confidence: 99%